Psycholinguistic Tools of Information and Psychological Influence in Captions Written under the Photographs - Kholod, Oleksandr (East European Journal of Psycholinguistics, 2016)
Despite the importance of information and psychological influence (IPI) of psycholinguistic tools used in captions written under the photographs, no attention has been paid to this topic, especially to the Nazi newspapers of Reichskommissariat Ukraine (RKU) which were published in 1941–1944. The aim of this study is to identify, describe and classify psycholinguistic tools of IPI used in captions written under the photographs in newspapers published in the period from 1 September 1941 to 10 November 1944 on the territory of the RKU and funded by the Nazi regime. The researcher refers to the following methods: observation, classification, summarization, content analysis, intent analysis, quantitative and qualitative methods. The present study analyzes the 81 captions placed under the 85 photographs in the newspapers published in the period from 1 September 1941 to 10 November 1944 on the territory of RKU and funded by the Nazi regime. The 8 groups (23 subgroups) of psycholinguistic tools of IPI were described and classified. The analysis shows that the most widely used psycholinguistic tools of IPI in RKU newspapers belong to the following two groups: the group "Germany" which is divided into 9 subgroups and to the group "Others" which is divided into 6 subgroups.ReferencesВоропаев С. Энциклопедия Третьего рейха [Текст] / С. Воропаев. – М.: Локид-Миф,1996.Voropayev, S. (1996). Entsiklopediya Tret'yego Reykha [The Encyclopedia of the ThirdReich]. Moscow: Lokid–Mif, 1996.Горевалов С. І. Фотокореспонденти й документальна фотографія періоду Другоїсвітової війни (до 70-річчя Великої Перемоги) / С. І. Горевалов // Наукові запискиІнституту журналістики. – 2014. – Т. 54. – С. 192–195.Gorevalov, S. (2014). Fotokorespondenty i Dokumental'na Fotografíya Períodu DrugoyiSvítovoyi Víyny (Do 70–Ríchya Velikoyi Peremogi) [Photocorrespondents andDocumentary Photograph During World War II]. Naukoví Zapyski Institutu Zhurnalistyki,54, 192–195.Горевалов С. І. Фотожурналістика в системі засобів масової комунікації: єдністьслова і зображення: навч. посіб. / С. І. Горевалов, Н. І. Зикун, С. А. Стародуб. – К.:КиМУ, 2010.  Gorevalov, S., N. Zikun, S. Starodub. (2010). Fotozhurnalístika v Systemí ZasobivMasovoyi Komuníkatsíyi: Yedníst' Slova í Zobrazhennya [Photo Journalism in the Systemof Mass Communication: The Unity of Word and Image]. Kyiv: KiMU.Двірна К. П., Левченко Ю. І. Рейхскомісаріати «Україна» та «Остланд» в періоднімецької окупації: особливості територіально-управлінської системи та політики /К. П. Двірна, Ю. І. Левченко // Грані. – № 3(107). – Березень 2014. – С. 106–114.Dvírna, K., Levchenko, Yu. (2014). Reykhskomísaríaty “Ukraína” ta “Ostland” v PeríodNímets'koyi Okupatsiyi: Osoblyvostí Teritoríal'no–upravlins'koyi Systemy ta Polítyky[Reichskomissariats “Ukraine” and “Ostland” During German Occupation: The Specific ofAdministrative Government and Politics]. Grani, 3(107), 106–114.Жуковський А., Субтельний О. Нарис історії України. – Л.: Вид-во НТШ, 1991. –С. 123.Zhukovs'kyi, A., Subtel'nyi, O. (1991). Narys Istoriyi Ukrayiny [An Outline of Histrory ofUkraine]. Lviv: NTS Publishers.Залесский К. А. Кто был в Третьем Рейхе. Библиографический, энциклопедическийсловарь [Текст] / К.А. Залесский. – М.: Астрель, 2003. – 942 с.Zalesskiy, K. A. (2003). Kto Byl v Tret'yem Reykhe. Bibliograficheskiy,entsiklopedicheskiy slovar' [Who Was in the Third Reich]. Moscow: Astrel.Івлєв І. О., Юденков А. Ф. Контрпропаганда підпільників і партизанів на окупованійрадянській території (1941–1944 pp.) // Український історичний журнал. – 1985. –№ 6. – С. 42.Ivlev, I., Yudenkov, A. (1985). Kontrpropaganda Pidpíl'nykív í Partyzanív na OkupovaníyRadyans'kíy Terytoríyi (1941–1944 rr.) [Counterpropaganda of the Underground Activistsand Partisans on the Occupied Soviet Territory] Ukrayinskyi Istorychyi Zhurnal, 6, 42.Коваль М. В. Общественно-политическая жизнь трудящихся Украинской ССР впериод Великой Отечественной войны. – К.: Наук, думка, 1977. – С. 203.Koval, M. (1977). Obshchestvenno–politicheskaya Zhizn' Trudyashchikhsya UkrainskoySSR v Period Velikoy Otechestvennoy Voyny [The Social and Poloitical Life of Workers ofthe Ukrainian SSR During the Great Patriotic War]. Kyiv: Naukova Doumka.Коваль М. В. Фашистская политика духовного, морально-политического подавлениянаселения Украины и ее крах (1941-1944) // Общественно-политическая жизньтрудящихся Украины в годы Великой Отечественной войны: Сб. науч. тр. – К.:Наук, думка, 1988. – С. 157.Koval, M. (1988). Fashistskaya Politika Dukhovnogo, Moral'no–politicheskogoPodavleniya Naseleniya Ukrainy i Yeyo Krakh (1941–1944). [The Fascist Policy ofSpiritual, Moral and Political Oppression of Ukrainian Citizens and Its Collapse]. In:Obshchestvenno–politicheskaya zhizn' trudyashchikhsya Ukrainy v gody VelikoyOtechestvennoy voyny, Kyiv: Naukova Doumka.Літвінюк О. В. Періодична преса як інформативне джерело з історії повсякденногожиття населення Донбасу в роки Великої Вітчизняної війни / О. В. Літвінюк //Історичні і політологічні дослідження. – № 3(53). – 2013. – С. 77–86.Lítvínyuk, O. (2013). Períodichna Presa yak Informativne Dzherelo z IstoriyiPovsyakdennoho Zhyttya Naselennya Donbasu v Roky Velikoíyi Vítchiznyanoyi Viyny[Periodical Press as an Information Source from the History of Everyday Life of theDonbas Inhabitants During the Great Patriotic War]. Istorychni i PolitolohíchniDoslidzhennya, 3(53), 77–86.Мальчевський І. Українська преса під німецькою окупацією // На зов Києва:Український націоналізм у II світовій війні: 3б. статей, спогадів і документів. –Торонто; Нью-Йорк: Новий шлях, 1985. – С. 291–295.Malchevskyi, I. (1985). Ukraíyinska Presa píd Nímets'koyu Okupatsíeyu [The UkrainianPress Under German Occupation]. Na Zov Kyieva: Ukrayinskyi Natsíonalízm u DryhiySvitiviy Viyni, 291–295.Мюллер. Н. Вермахт и оккупация [Текст] / Н. Мюллер. – М.: Вече, 2010.Mueller, N. (2010). Vermakht i okkupatsiya [Vermacht and Occupation]. Moscow: Veche.Немецко-фашистский оккупационный режим (1941-1944 гг.) [Текст] / Ред.С. Бубеншиков. – М.: Политиздат, 1965.Nemetsko–fashistskiy Okkupatsionnyy Rezhim (1941–1944 gg.) [German FascistOccupation Regime (1941-1944)]. (1965). S. Bubenshikov, Ed. Moscow: Politizdat.Німецько-фашистський окупаційний режим на Україні. Збірник документів іматеріалів [Текст] / Ред. П. М. Костриби та ін. – К.:Державне видавництвополітичної літератури, 1963.Nímets'ko–fashists'kiy okupatsíyniy Rezhym na Ukrayini. [German Fascist OccupationRegime in Ukraine] (1963). P. M. Kostribi, Ed., Kyiv: Derzhavne VydavnytstvoPolitychnoyi Líteratury.Преступные цели – преступные средства: Документы об оккупационной политикефашистской Германии на территории СССР (1941-1944 гг.) [Текст] / Сост.Г. Ф. Заставенко. – М.: Экономика, 1985.Prestupnyye tseli – prestupnyye sredstva: Dokumenty ob okkupatsionnoy politikefashistskoy Germanii na territorii SSSR (1941–1944 gg.) [Crimnal Goals – CriminalMeans]. (1985). G. F. Zastavenko, Ed. Moscow: Ekonomika.Стафийчук И. П. Комсомол Украины в партизанском движении 1941–1944 гг.:(Полит, работа среди населения оккупированных районов). – М.: Мысль, 1968. –С. 26.Stafiychuk, I. P. (1968). Komsomol Ukrainy v Partizanskom Dvizhenii 1941–1944 gg .:(Politrabota sredi naseleniya okkupirovannykh rayonov), [The Komsomol of Ukarine inthe Partisan Movement 1941 – 1945]. Moscow: Mysl.Титаренко Д. М. Преса Східної України періоду німецько-фашистської окупації якісторичне джерело (1941–1943 pp.): дис. ... к. і. н.: 07.00.06. / Донецький нац. ун-т. –Донецьк, 2002. – С. 45–46.Titarenko, D. (2002). Presa Skhidnoyi Ukrayiny Periodu Nimets'ko-fashists'koyiOkupatsíyi yak Istorychne Dzherelo (1941–1943 rr. [The Press of Eastern Ukraine DuringGerman fascist Occupation as a Historical Source]. Ph.D. dissertation. Donetsk: Donets'kNational University.Толанд Дж. Адольф Гитлер / Дж. Толанд. – Том 1. – М.– Мн.– Калининград: Интердайджест, 1993.Toland, G. (1993). Adolf Hitler. Vol. 1. Moscow; Minsk; Kaliningrad: Inter-Digest.Толанд Дж. Адольф Гитлер / Дж. Толанд. — Том 2. — М.–Мн.–Калининград: Интердайджест, 1993.Toland, G. (1993). Adolf Hitler. Vol. 2. Moscow; Minsk; Kaliningrad: Inter–Digest.Холод О. М. Преса Рейхскомісаріату «Україна» і сучасні медіа: монографія /О. М. Холод. – К.: КНУКіМ, 2016.Kholod, O. (2016). Presa Reykhskomísaríatu “Ukrayina” í Suchasní Medía [The UkraineReichskommissariat Press and Modern Media]. Kyiv: Kyiv National University of Cultureand Art..Черняков Б. І. Періодична преса на окупованій території України / Б. І. Черняков //Наукові записки Інституту журналістики [Електронне видання]. – Режим доступу:http://journlib.univ.kiev.ua/index.php?act=article&article=1648.Chernyakov, B. Periodychna Presa na Okupovaniy Terytoríyi Ukrayiny [ThePeridical Press on the Occupied Territory]. Naukovi Zapyski InstitutuZhurnalistyky. Retrieved from: http://journlib.univ.kiev.ua/ index.php?act=article&article=1648.Черняков Б. І. Окупаційна преса Рейхскомісаріату Україна / Б. І. Черняков // 3б.праць Науково-дослідного центру періодики Львівської національної бібліотекиімені В. Стефаника. – Л., 2003. — С. 152–159.Chernyakov, B. (2003). Okupatsiyna Presa Reichskomisariatu Ukrayiny [The UkraineReichskommissariat Press During the Occupation Period]. Bulletin of the Research Centerfor Periodicals of Lviv vasyl Stefanyk National Library, 152–159.Шаповал Ю. Г. Изображение и слово в журналистике / Ю. Г. Шаповал. — Львов :Вища школа, 1985.Shapoval, Yu. (1985). Izobrazheniye i Slovo v Zhurnalistike [The Image and Word inJournalism]. Lviv: Vyshcha Shkola.Die Presse im Reichskornmissariat Ukraine. The State Archive of Rivne Oblast. F. Р-22,on. 1 page. 149. 21–27.